An Interpretive Description of Women's Experience in Coordinated, Multidisciplinary Treatment for an Eating Disorder - Kary Woodruff; Lauren Clark; Elizabeth Joy; Scott A. Summers; Julie M. Metos; Nica Clark; Kristine C. Jordan (SAGE Publishing, 2020)
Coordinated, multidisciplinary treatment for women with eating disorders is consistently recommended as maximally effective, but few studies have considered the patient experience. This qualitative study examined the experiences of women receiving such care in an outpatient setting. Using an interpretive description methodology, we conducted 12 in-depth interviews with participants who were diagnosed with an eating disorder and were receiving team-based treatment. Patients uniformly advocated for the coordinated, multidisciplinary treatment approach. Analysis of participants' experiences yielded four categories: relying on the lifeline of communication, supporting autonomy, drawing on individual strengths, and valuing synergy. These findings build on previous research emphasizing the importance of autonomy support and connectedness in the recovery process from an eating disorder. Findings highlight the importance of nurses to support a multidisciplinary care approach to working with this patient population; these women's voices also support a treatment approach that, despite being widely recommended, is vastly understudied and underutilized.